Enterovirus infection and type 1 diabetes: unraveling the crime scene - Rodriguez‐Calvo, T. (Clinical and experimental immunology, 2019)
Summary Enteroviruses (EV) have been historically associated to type 1 diabetes. Definitive proof for their implication in disease development is lacking, but growing evidence suggests that they could be involved in beta cell destruction either directly by killing beta cells or indirectly by creating an exacerbated inflammatory response in the islets, capable of attracting autoreactive T cells to the ‘scene of the crime’. Epidemiological and serological studies have been associated with the appearance of islet autoimmunity and EV RNA has been detected in prospective studies. In addition, the EV capsid protein has been detected in the islets of recent‐onset type 1 diabetic donors, suggesting the existence of a low‐grade EV infection that could become persistent. Increasing evidence in the field shows that a ‘viral signature’ exists in type 1 diabetes and involves interferon responses that could be sustained during prolonged periods. These include the up‐regulation of markers such as protein kinase R (PKR), melanoma differentiation‐associated protein 5 (MDA5), retinoic acid inducible gene I (RIG‐I), myxovirus resistance protein (MxA) and human leukocyte antigen‐I (HLA‐I) and the release of chemokines able to attract immune cells to the islets leading to insulitis. In this scenario, the hyperexpression of HLA‐I molecules would promote antigen presentation to autoreactive T cells, favoring beta cell recognition and, ultimately, destruction. In this review, an overview is provided of the standing evidence that implicates EVs in beta cell ‘murder’, the time‐line of events is investigated from EV entry in the cell to beta cell death and possible accomplices are highlighted that might be involved in beta cell demise.